Islamic Moderation of Ibn Rushd’s Thoughts to Counter Radicalism in Indonesia - Mamdukh Budiman; Mirza Mahbub Wijaya (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This paper discusses the moderation attitude to counter radicalism in Indonesia. Why is this research interesting to discuss? Fundamentalism is dammed by education and understanding of diversity. Therefore, the author offers the thoughts and personality of Ibn Rushd. In historical records, Ibn Rushd is a scholar who never attacks personally and accuses his opponents of infidelity. The moderation attitude showed by Ibn Rushd can be used as a model for character building for Muslims today. In terms of methodology, this article is of library research type. Furthermore, the writer digs up data from Ibn Rushd’s books and uses a philosophical approach with content analysis or hermeneutics. According to Ibn Rushd, a scholar must have several essential moderation personalities. There are three parts: before, in, and after thinking. Before thinking, a scholar must have an open, honest, curious, sceptical, courageous, and patient personality. Scholars’ personality in thinking is speculative, willing to be guided by experience and reason, willing to accept, ready to face mistakes and dare to make decisions. Furthermore, the personality, after thinking, are tolerant and forgiving